Students' perception towards task-based language teaching (TLBT) approach in learning Arabic language: CFS, IIUM experience - Hashim, Marzidah; Raja Sulaiman, Raja Munirah; Selamat, Nita Fauzee; Arshad, Mastura (2014)
Task-Based Language Teaching (TBLT) is a new approach in teaching second language particularly in Arabic language. The approach, which employs student-centred approach, is viewed as more effective than the traditional way. This approach is slowly gaining its popularity among Arabic language educators and learners all around the world. In Malaysia, the Centre for Foundation Studies, International Islamic University Malaysia (CFSIIUM) is one of the first institutions of education to implement this new way in teaching Arabic language. As such, this study was conducted in order to find out the students’ perception towards the implementation of task-based language teaching (TBLT) in this learning institution. 313 respondents were randomly selected from the students in Arabic elementary level studying at CFSIIUM. The instrument used in the survey was survey questionnaires. The quantitative results were used to examine students’ perception towards the implementation of task-based language teaching (TBLT) in Arabic language. The findings indicated that the respondents were positive in learning Arabic language using this approach and they were motivated to learn this language.